2022
DOI: 10.1136/bmjopen-2022-064304
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for the development of SPIRIT and CONSORT extensions for randomised controlled trials with surrogate primary endpoints: SPIRIT-SURROGATE and CONSORT-SURROGATE

Abstract: IntroductionRandomised controlled trials (RCTs) may use surrogate endpoints as substitutes and predictors of patient-relevant/participant-relevant final outcomes (eg, survival, health-related quality of life). Translation of effects measured on a surrogate endpoint into health benefits for patients/participants is dependent on the validity of the surrogate; hence, more accurate and transparent reporting on surrogate endpoints is needed to limit misleading interpretation of trial findings. However, there is cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…Although correlation coefficients and coefficients of determination from meta-analyses of clinical trials are often used to evaluate the strength of association between surrogate markers and clinical outcomes, these values are purely statistical, rely on arbitrary cutoffs, and fail to capture information about the study design, target outcome, and generalizability of the evidence. Although more comprehensive methods to establish surrogacy have been proposed (eg, the Biomarker-Surrogacy Evaluation Schema), enhanced clinical trial reporting and greater availability of shared individual patient-level data will facilitate more precise analyses and estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Although correlation coefficients and coefficients of determination from meta-analyses of clinical trials are often used to evaluate the strength of association between surrogate markers and clinical outcomes, these values are purely statistical, rely on arbitrary cutoffs, and fail to capture information about the study design, target outcome, and generalizability of the evidence. Although more comprehensive methods to establish surrogacy have been proposed (eg, the Biomarker-Surrogacy Evaluation Schema), enhanced clinical trial reporting and greater availability of shared individual patient-level data will facilitate more precise analyses and estimates.…”
Section: Discussionmentioning
confidence: 99%
“…While accepting treatment effects on a biomarker as a replacement for a target outcome has become increasingly commonplace in the regulatory setting, [7][8][9] there has been much less consideration for the use and implications of intermediate outcomes as surrogate endpoints in the wider context of healthcare interventional trials. [11][12][13] As part of the development of the SPIRIT and CONSORT extensions for the reporting of RCTs with a primary surrogate endpoint, 16 we undertook four linked empirical studies (a scoping review, e-Delphi study, consensus meeting, and a web survey) to inform the development of a definitional framework for the improved design, reporting, and interpretation of trials using surrogate endpoints. Our e-Delphi study showed good support for the 2016 BEST (Biomarkers, Endpoints, and other Tools) definition from the NIH-FDA Working Group that biomarkers (e.g., brain amyloid plaque protein, blood pressure, tumour response) can act as surrogate endpoints in interventional trials by acting as a substitute and predictor of treatment effects on target outcome(s) for how a patient feels, functions, and survives.…”
Section: Discussionmentioning
confidence: 99%
“…As part of a UK Medical Research Council-funded project to develop the CONSORT (Consolidated Standards of Reporting Trials) and SPIRIT (Standard Protocol Items: Recommendations for Interventional Trials) extensions for RCT protocols and final reports using surrogate endpoints, we undertook four linked empirical studies to examine the definition and interpretation of surrogate endpoints in trials. 16 , 17 This included a scoping review of current surrogate endpoint definitions, rated for their acceptability and clarity as part of an e-Delphi study, and assessment in a hybrid consensus meeting with an extension of the e-Delphi study to gauge how a sample of international stakeholders (including clinicians, trial investigators, patients and public partners, journal editors, and health technology experts) approached the judgment of intermediate outcomes in RCTs as a surrogate endpoints or target outcomes. We present a summary of these empirical studies and, using their findings, propose a definitional framework to inform the better reporting of trials using surrogate endpoints and to aid stakeholders' (including patients, clinicians, regulators, and payers) in their interpretation of surrogate endpoint evidence.…”
Section: Introductionmentioning
confidence: 99%
“…The structure and writing of this protocol were guided by the recently published protocol for the SPIRIT-SURROGATE and CONSORT-SURROGATE extensions (12).…”
Section: Methodsmentioning
confidence: 99%
“…However, the meeting time will be sufficient to allow discussion time for all items. Other extensions have used meetings over two days (4,5,12).…”
Section: Structure and Participantsmentioning
confidence: 99%